Identifikasi Sistem Operasi Prosedur Tingkat Penanganan Penyakit pada Anak Balita - Samosir, Khairunnisa; Yunus, Yuhandri (Jurnal Informasi dan Teknologi, 2020)
Children at the age of 1 year (toddlers) are more susceptible to the disease, parents must always give more attention to their children with poor health conditions, of course it will be very important for the growth of children. Application of an expert system to diagnose digestive diseases by using the forward chaining method can help parents in knowing the state of children's health. This research is an applied technology product that can provide benefits as a media or instructor in handling patients. The design of this system has been carried out through data activities, rule design, process design and system testing. From data and information found handling facts. The results obtained from system testing using the PHP MySQl application indicate that the results of diagnoses and pediatric diseases at Tanjung Balai General Hospital, have as many as 10 patient data that have been examined by experts and have conducted system checks to achieve 80% accuracy, from the conclusions that can be concluded data obtained from experts developed using the Forward Chaining Method are appropriate in determining the symptoms and diseases obtained from experts.